PENGARUH ETOS KERJA TERHADAP PRODUKTIVITAS SALES INDOMOBIL NISSAN DATSUN PADANG - Dea Emilta; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The importance of vehicles for the modernization era as a means of transportation requires companies to improve their quality to attract public interest and maintain the company's existence in the midst of existing competition. PT Wahana Wirawan Riau Indomobil Nissan Khatib Sulaiman Padang is the only Nissan Datsun branch office in the West Sumatra area that has to work hard to reach people in West Sumatra Province. Sales as the spearhead of the company are expected to increase sales, so they must have a good work ethic in order to have a good impact on sales productivity, this is based on Max Weber's thinking about work ethics. The purpose of this study was to find out how the sales marketing work ethic and sales productivity and see the effect of work ethic on sales productivity. The research method used in this research is descriptive quantitative. The results of the study indicate that in general sales marketing already has a high work ethic and most of the sales productivity of sales marketing is in the medium category. The relationship between work ethic and sales productivity is strong with a value of r 0.721. Furthermore, there is a positive and significant influence of work ethic variables on work productivity, this is indicated by the t count value of 4.648 which is greater than t table. The contribution of work ethic to sales productivity is 51.9%, while the rest is influenced by other variables not examined in this study.Keywords : Work Ethic, Productivity, Sales Marketing.